Nitric Oxide, Oxidative Stress, and p66Shc Interplay in Diabetic Endothelial Dysfunction. (5th March 2014) - Magenta, Alessandra; Greco, Simona; Capogrossi, Maurizio C.; Gaetano, Carlo; Martelli, Fabio
Abstract : Increased oxidative stress and reduced nitric oxide (NO) bioavailability play a causal role in endothelial cell dysfunction occurring in the vasculature of diabetic patients. In this review, we summarized the molecular mechanisms underpinning diabetic endothelial and vascular dysfunction. In particular, we focused our attention on the complex interplay existing among NO, reactive oxygen species (ROS), and one crucial regulator of intracellular ROS production, p 66 S h c protein.